2014
DOI: 10.1007/s11302-014-9436-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac purinergic signalling in health and disease

Abstract: This review is a historical account about purinergic signalling in the heart, for readers to see how ideas and understanding have changed as new experimental results were published. Initially, the focus is on the nervous control of the heart by ATP as a cotransmitter in sympathetic, parasympathetic, and sensory nerves, as well as in intracardiac neurons. Control of the heart by centers in the brain and vagal cardiovascular reflexes involving purines are also discussed. The actions of adenine nucleotides and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 750 publications
(354 reference statements)
1
99
0
4
Order By: Relevance
“…Clinical studies found that the removal of the SCG and other cervical sympathetic ganglia ameliorate 50-60 % of angina symptoms in patients with coronary heart disease [53,54]. P2X receptors are involved in cardiovascular function and disease [11,[13][14][15]55]. Previous studies from our laboratory showed that the upregulation of the P2X 7 receptors in the cervical sympathetic ganglia (SG or SCG) after MI injury resulted in a increase in blood pressure and HR [18,21,22,24,29].…”
Section: Discussionmentioning
confidence: 91%
“…Clinical studies found that the removal of the SCG and other cervical sympathetic ganglia ameliorate 50-60 % of angina symptoms in patients with coronary heart disease [53,54]. P2X receptors are involved in cardiovascular function and disease [11,[13][14][15]55]. Previous studies from our laboratory showed that the upregulation of the P2X 7 receptors in the cervical sympathetic ganglia (SG or SCG) after MI injury resulted in a increase in blood pressure and HR [18,21,22,24,29].…”
Section: Discussionmentioning
confidence: 91%
“…2 In 1978, separate families of receptors for adenosine (P1) and ATP and ADP (P2) were recognized, 3 and purine and pyrimidine receptors were cloned and characterized in the early 1990s. 4 Four P1 G-proteincoupled receptor subtypes (A 1 , A 2A , A 2B , and A 3 ), 7 P2X ion channel receptor subtypes (P2X1-7), and 8 P2Y G-proteincoupled receptor subtypes (P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , P2Y 11 , P2Y 12 , P2Y 13 , and P2Y 14 ) are recognized. 5 ATP is released by gentle mechanical stimulation from most, if not all, cell types, as well as from dead or dying cells.…”
mentioning
confidence: 99%
“…8,9 There are both short-term purinergic signaling in neurotransmission, neuromodulation, and secretion and long-term (trophic) purinergic signaling in cell proliferation, differentiation, and death in development and regeneration. 10 Reviews on various aspects of purinergic signaling in cardiac physiology and pathophysiology have been published, including: physiological roles of cardiac P2X and P2Y purinoceptors, 11 roles of adenosine in health and disease, 12 effects of ATP and adenosine on coronary myocytes, 13 purine degradation pathways in the myocardium, 14 myocardial nucleotide transport, 15 nonadrenergic, noncholinergic neural control of the atrial myocardium, 16 vagal cardiovascular reflexes, 17 and genetic modulation of adenosine receptor function.…”
mentioning
confidence: 99%
“…The P2X 7 receptor plays important roles in the pathological process of inflammation or ischemic injury [2,9,21,27,42,45], and purinergic signaling participates in the regulation of sympathetic function [43,46]. P2X receptors can be activated by ATP, and ATP released from damaged cells may upregulate and activate the P2X 7 receptor and initiate neuronal injury [2,24,27,49,50]. The upregulated expression of P2X 7 mRNA and protein in PC12 cells is related to OGD [34].…”
Section: Discussionmentioning
confidence: 99%